2023
DOI: 10.1107/s1600576723009731
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade of the small-angle neutron scattering diffractometer SANS-J at JRR-3

Takayuki Kumada,
Ryuhei Motokawa,
Yojiro Oba
et al.

Abstract: The small-angle neutron scattering diffractometer SANS-J at the research reactor JRR-3, Tokai, Japan has been upgraded. A 3He front detector was installed adjacent to the direct beam just behind the sample position to cover scattering in the range 1.3–6 nm−1 for the magnitude of the scattering vector Q. Additionally, the maximum Q covered by the existing main 3He detector was extended to 1.8 nm−1 by decreasing the minimum sample-to-detector distance. These modifications enabled gapless measurements of the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We recently reconsidered the structure and conformation of several water-soluble, chemically modified cellulose ether samples in aqueous solution. It has been widely believed that most water-soluble, chemically modified cellulose derivatives behave as semiflexible polymer chains with finite persistence lengths, e.g., 5–20 nm, in aqueous solution. However, we found that methyl cellulose (MC) samples with a degree of substitution (DS) = 1.8, hydroxyethyl cellulose (HeC) samples with a molar substitution number, MS, ∼2.4, and hydroxypropylmethyl cellulose (HpMC) samples with a DS = 1.9 and MS ∼ 0.25 possess formation factors that can be reasonably described with rod particles in aqueous solution, as in the case of the HpC samples in this study. These systems maintained the relationship L / R g ∼ 3.5 characteristic of the rod particles over the M w range examined and demonstrated an increasing change in l c / L data from 2 in the lower M w range to 4 (or more) in the range of M w > 300 kg mol –1 with increasing M w . Reformation of intramolecular hydrogen bonds between hydroxyl groups on chemically modified cellulose samples is essential for rod-like particle formation. The reason why the dependence of l c / L on M w in the HpC samples found in this study is substantially distinct from that observed in aqueous systems of MC, HeC, and HpMC should be that the molar substitution number, MS, is ∼3.8, which is markedly greater than those of the MC, HeC, and HpMC samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reconsidered the structure and conformation of several water-soluble, chemically modified cellulose ether samples in aqueous solution. It has been widely believed that most water-soluble, chemically modified cellulose derivatives behave as semiflexible polymer chains with finite persistence lengths, e.g., 5–20 nm, in aqueous solution. However, we found that methyl cellulose (MC) samples with a degree of substitution (DS) = 1.8, hydroxyethyl cellulose (HeC) samples with a molar substitution number, MS, ∼2.4, and hydroxypropylmethyl cellulose (HpMC) samples with a DS = 1.9 and MS ∼ 0.25 possess formation factors that can be reasonably described with rod particles in aqueous solution, as in the case of the HpC samples in this study. These systems maintained the relationship L / R g ∼ 3.5 characteristic of the rod particles over the M w range examined and demonstrated an increasing change in l c / L data from 2 in the lower M w range to 4 (or more) in the range of M w > 300 kg mol –1 with increasing M w . Reformation of intramolecular hydrogen bonds between hydroxyl groups on chemically modified cellulose samples is essential for rod-like particle formation. The reason why the dependence of l c / L on M w in the HpC samples found in this study is substantially distinct from that observed in aqueous systems of MC, HeC, and HpMC should be that the molar substitution number, MS, is ∼3.8, which is markedly greater than those of the MC, HeC, and HpMC samples.…”
Section: Resultsmentioning
confidence: 99%
“…SANS measurements were carried out using a small-angle neutron scattering instrument (SANS-J) installed in Japan Research Reactor-3 (JRR-3) at the Japan Atomic Energy Agency (Tokai). Two camera lengths, 10 and 2 m, were used, and the magnitude of the scattering vector, q , covered by the SANS experiments ranged from 2.5 × 10 –2 to 5.0 nm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…PXRD patterns were acquired on an X-ray diffractometer (MiniFlex600, Rigaku Co. Ltd, Japan) with Cu-K α radiation. Small-angle neutron scattering (SANS) experiments were performed for swollen hydrogel samples using a SANS diffractometer with sample-to-detector distance of 2 and 10 m, SANS-J 15 at the research reactor, JRR-3. The details of characterization were described in the ESI †…”
Section: Methodsmentioning
confidence: 99%
“…SANS measurements were carried out using a SANS-J diffractometer at the Japan Research Reactor-3 (JRR-3) of the Japan Atomic Energy Agency (JAEA) in Tokai, Japan. 41 The incident neutron beam was monochromated using a velocity selector with a wavelength (λ) of 0.65 nm and a wavelength distribution (Δλ/λ) of 0.15. The incident beam size was defined using a 20 × 20 mm 2 aperture 10 m upstream of the samples and a 15 mm diameter aperture at the sample position.…”
Section: Methodsmentioning
confidence: 99%